2007
DOI: 10.1038/sj.leu.2404940
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes are activated in patients with myelodysplastic syndromes and can contribute to bone marrow failure through CD40–CD40L interactions with T helper cells

Abstract: Immune mechanisms have been shown to contribute to the process of myelodysplastic syndromes (MDS)-related bone marrow (BM) failure. The aim of this study was to evaluate the possible contribution of activated monocytes through CD40-CD40L(CD154) interactions with activated T helper cells. We demonstrated in 77 predominantly lower risk MDS patients that the CD40 receptor was expressed significantly higher on monocytes and that CD40L was expressed significantly higher on T helper cells in peripheral blood (PB) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In conclusion, we find that monocyte composition, monocyte LPS response, and monocyte phagocytic ability are relatively unchanged in peripheral blood from patients with MDS. A prior study indicated that monocytes from MDS patients exhibit an increased response to CD40 activation. Coupled with the increased MHC Class II production observed in the current study, this may suggest that the enhanced ability to present antigen and activate T cells could compensate, at least in part, for decreased neutrophil function present in these patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we find that monocyte composition, monocyte LPS response, and monocyte phagocytic ability are relatively unchanged in peripheral blood from patients with MDS. A prior study indicated that monocytes from MDS patients exhibit an increased response to CD40 activation. Coupled with the increased MHC Class II production observed in the current study, this may suggest that the enhanced ability to present antigen and activate T cells could compensate, at least in part, for decreased neutrophil function present in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes from patients with chronic lymphocytic leukemia (CLL) exhibit significant immune dysfunction including an altered monocyte profile and a diminished inflammatory response induced by LPS . However, the function (or dysfunction) of monocytes in MDS patients remains unclear; the few prior studies concerning this topic have suggested that these immune cells may retain significant function …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings might support a positive effect of azacytidine maintenance in this group but could also just reflect a more robust response to induction chemotherapy. There are previous reports of differences in the immune response between MDS patients with trisomy 8 and other MDS (Kawabata et al, 2006;Meers et al, 2007) and also on the immunomodulatory effects of azacytidine (Laurenzana et al, 2009;Liu et al, 2009;Sánchez-Abarca et al, 2010). Whether immunomodulation, by demethylation or not, may explain the better overall outcome in this group remains to be studied.…”
Section: Discussionmentioning
confidence: 95%
“…The etiology of bone marrow (BM) failure in MDS is not yet fully understood but is multifactorial and caused by intrinsic defects in the HSC (e.g., mutations in AML1, EVI1, NUP98 and NUP214) as well as extrinsic defects in the BM niche [3]. The latter include excess production of, for example, tumor necrosis factor-α and interferon-γ, abnormalities in endothelial cells, mesenchymal stromal cells (MSCs) and osteoblasts (cells that are part of the HSC niche) and activation of T lymphocytes, monocytes and dendritic cells leading to abnormal proliferation and differentiation of HSCs [4][5][6][7][8][9].The only curative therapy is allogeneic HSC transplantation, which is suitable for only a minority of the patients due to advanced age. Recently, three drugs have been approved by the U.S. Food and Drug Administration: decitabine, lenalidomide and 5-azacitidine (the last two are also approved by the European Medicines Agency); in a subgroup of MDS patients, these drugs decrease cytopenias, induce cytogenetic remission and reduce BM blasts, while not completely eradicating the malignant HSC clone [10].…”
Section: Introductionmentioning
confidence: 99%